2017
DOI: 10.1007/s10551-017-3542-2
|View full text |Cite
|
Sign up to set email alerts
|

Everyday-Life Business Deviance Among Chinese SME Owners

Abstract: Despite its prevalence in emerging economies, everyday-life business deviance (EBD) and its antecedents have received surprisingly little research attention.Drawing on strain theory and the business-ethics literature, we develop a socio-psychological explanation for this deviance. Our analysis of 741 owners of Chinese small-and medium-sized enterprises (SMEs) suggests that materialism and trust in institutional justice affect EBD both directly and indirectly in a relationship mediated by the ethical standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
(191 reference statements)
0
8
0
Order By: Relevance
“…Before that, Siemens paid US$800 million and KBR/Halliburton paid more than US$560 million when it was found guilty of paying bribes to get some energy contracts in Nigeria (Koehler, 2010). Thus, while large multinational corporations are frequently audited for compliance with anti-corruption laws (Weismann, 2009), much less attention is paid to smaller firms, even though small medium enterprises have been recognised as a foundation for economic growth and national development (Ji et al, 2019). There are however reports on combating bribery in the small and mediumsized enterprises (SME) sector of the ACCA (2019) and recommendations to prevent corruption among SMEs to foster their development (United Nations Industrial Development Organization [UNIDO] & United Nations Office on Drugs and Crime [UNODC], 2012).…”
Section: The Cost Of Briberymentioning
confidence: 99%
“…Before that, Siemens paid US$800 million and KBR/Halliburton paid more than US$560 million when it was found guilty of paying bribes to get some energy contracts in Nigeria (Koehler, 2010). Thus, while large multinational corporations are frequently audited for compliance with anti-corruption laws (Weismann, 2009), much less attention is paid to smaller firms, even though small medium enterprises have been recognised as a foundation for economic growth and national development (Ji et al, 2019). There are however reports on combating bribery in the small and mediumsized enterprises (SME) sector of the ACCA (2019) and recommendations to prevent corruption among SMEs to foster their development (United Nations Industrial Development Organization [UNIDO] & United Nations Office on Drugs and Crime [UNODC], 2012).…”
Section: The Cost Of Briberymentioning
confidence: 99%
“…Individuals are likely to behave unethically when feeling angry (Kligyte et al, 2013) or anxious (Kouchaki & Desai, 2015), but to behave ethically when feeling fearful (Kligyte et al, 2013) or guilty (Motro et al, 2018). This is relevant because minor everyday-life business deviance, that is the little actions individuals take to maximize profit, such as a "request for cash payment to avoid paying taxes" in the informal sector, can add up and produce differential effects at large (Ji et al, 2019(Ji et al, , p. 1179. Scholars could thus address pending questions about unethical behavior (e.g., Baron et al, 2015) and beyond by considering the temporal influence of discrete emotions.…”
Section: Affectmentioning
confidence: 99%
“…Participants' weekly work hours can influence their interpersonal work behaviors because fewer hours may motivate employees to work harder to establish new relationships (Harari et al, 2017). We also controlled for the effect of social desirability on interpersonal deviant behaviors because previous studies have shown that individuals may tend to deny socially undesirable behaviors (Ji et al, 2019). Thus, we measured social desirability using a 12-item scale from Reynolds (1982).…”
Section: Control Variablesmentioning
confidence: 99%